Growth performance and pork quality of two New Zealand pig genotypes : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Physiology at Massey University, Palmerston North, New Zealand - Kerr, Steven James (Massey University, 2012)
In the pig industry, feed is a major cost which contributes 60 - 80% of production costs, thus it is important that feed specifications reflect the needs for modern genotypes to express their genetic growth potential. The major genetic drivers for growth are the minimum whole body lipid to protein ratio (Minlp) and the upper limit to protein deposition (Pdmax). The objective of the present study was to evaluate the growth performance potential and pork quality of two genotypes (G1 and G2) commonly used in New Zealand. Sixty four pigs were reared indoors for 12 weeks, and fed two diets to slaughter. The first diet was limited in energy (to provide expression of Minlp); and the second was not limited in energy or protein/amino acids (to provide expression of Pdmax). After slaughter, carcass measurements were recorded and pork quality was tested. During the Minlp and Pdmax diet phases the key overall findings were that G1 had improved average daily gain (940 vs. 890 g/d) and feed conversion ratio (1.75 vs. 1.87), had lower calculated Minlp slope (i.e., 0.0248, 0.0327) and greater Pdmax values (i.e., 226 vs. 204 g/d) compared to G2. No difference was found for daily feed intake. For carcass traits G1 had the lower backfat thickness. There was no difference found for dressing % or carcass weight. For pork quality, G2 had the lower pH and also had greater thawloss % compared to G1. In conclusion G1 had overall better growth performance and were leaner than G2. The pork from both G1 and G2 was not found to have pale soft and exudative (PSE) quality and was considered to be very tender.
Keywords: Swine; Pigs; New Zealand pig genotypes; Minlp diet; Pdmax diet; Growth; Pork quality